A Review on Characterization of Sediments for Green Bricks Production - Ean, L. W.; Malek, M. A.; Mohammed, Bashar S.; Tang, Chao-Wei; Bong, P. X. H. (International Journal of Engineering and Technology, 2018)
Accumulation of dredged sediment has raised environmental concern in various countries. Recycling of sediment into bricks is a viable solution to the environmental pollution. Concerning to the utilization of sediment in bricks, this study reviews the needs of characterization on sediment and methods of producing sediment bricks. Particle size distribution was found to be the key criteria for characterization of sediment. Sizes of particles determined the function of the sediments in the bricks. In spite of that, leachability of heavy metals is another important aspect for contaminated sediment. Cementing bricks used cementing materials as the stabilization agent to the heavy metals. It is necessary to conduct leaching test for the end-product of the sediment to ensure the heavy metals leached are within the regulatory limits. In conclusion, method of producing sediment bricks may vary due to the various characteristics of sediment for a promising environmental friendly production.